A set of olefin metathesis catalysts with extraordinary stickiness to silica - Schachner, Jörg A.; Cabrera, José; Padilla, Robin; Fischer, Christoph; van der Schaaf, Paul A.; Pretot, Roger; Rominger, Frank; Limbach, Michael (ACS catalysis, 2011)
We report on a series of six new pyridinealkoxide-bridged first and second generation ruthenium carbenes with similar or even higher activity in ring-opening metathesis polymerization (ROMP), cross metathesis (CM), and ring closing metathesis (RCM) reactions than state-of-the-art catalysts. The new precatalysts show an extraordinarily high stickiness to commercially available silica, which significantly enhances their adsorptive separation from unprocessed reaction mixtures.